Antidiabetic Activity Test of Ethanol Extract Combination of Moringa Oleifera L. Leaves and Snakehead Fish (Channa Striata) - Salsabila Fitriyanti; Tri Fitri Yana Utami; Nikmah Nuur Rochmah (Indonesian Journal of Pharmacy and Natural Product, 2025)
Diabetes mellitus DM is a serious global health issue caused by the body's inability to use insulin optimally, resulting in uncontrolled blood sugar levels. Moringa leaves Moringa oleifera L. and snakehead fish Channa striata are known to have antidiabetic potential; moringa leaves contain quercetin, while snakehead fish are rich in arginine and leucine, which help regulate blood sugar levels. This study aims to test the antidiabetic activity of the combination of Moringa oleifera L. leaf ethanol extract and Channa striata ethanol extract CMOCS in male white mice. A total of 25 Wistar rats were divided into five groups: negative control distilled water, positive control glibenclamide 0.45 mg/kg body weight, and three combination groups of CMOCS 100, 200, 300 mg/kg body weight. Diabetes was induced by alloxan. Blood glucose levels were measured on days 0, 7, and 14. The results showed that alloxan successfully induced hyperglycemia. After 14 days, all combination groups reduced blood glucose levels. CMOC III  was the most effective, reducing glucose levels by 31.91%, approaching glibenclamide 37.78%. The Mann-Whitney test showed significant differences CMOCS I produced a p-value of 0.021, CMOCS II a p-value of 0.036, and CMOCS III a p-value of 0.047 p < 0.05 between the negative control and the treatment groups, confirming the antidiabetic activity of this extract combination.